Wisata Halal dalam Konteks Kearifan Lokal Kampung Adat Cireundeu di Kota Cimahi Berdasarkan Fatwa DSN-MUI No. 108/DSN-MUI/X/2016 - Nur Fadilah Sukmawardani; Popon Srisusilawati; Nandang Ihwanudin (UNISBA Press, 2023)
Abstract. In 2019 Indonesia ranked first as the country with the best halal tourist destination according to GMTI (Global Muslim Travel Index). West Java is one of the provinces developing National Priority halal tourism destinations. But in reality there are still tours in West Java that do not meet the criteria as halal tourist destinations when viewed from Fatwa DSN-MUI No.108 of 2016 concerning Guidelines for organizing tourism based on sharia principles. Cireundeu traditional village located in West Java is one of the tourist destinations that has unique local wisdom. The research aims to analyze the practice of halal tourism in the context of local wisdom in Cireundeu Traditional Village with a review of the DSN-MUI Fatwa. The method of writing this thesis uses normative legal research methods using a qualitative approach which uses data collection techniques by collecting and describing data obtained through library research and field research by conducting interviews, which then the results of the research will be presented in the form of words. Halal tourism in the context of local wisdom is actually quite difficult to implement in Cireundeu Traditional Village. However, for Cireundeu Traditional Village halal tourism is not something that must be avoided by the managers and people of Cireundeu Traditional Village. However, for Cireundeu Traditional Village halal tourism is not something that must be avoided by the manager and the people of Cireundeu Traditional Village. In the review by Fatwa DSN-MUI, there are also several aspects of halal tourist destinations that are not appropriate or fulfilled on the Cireundeu Traditional Village tour. For the management, it would be better if they improve facilities such as the construction of places of worship that are strategically located to the tourist center, to make it easier for Muslim tourists who will perform worship. The Indonesian Ulema Council and the Ministry of Religious Affairs should socialize the provisions relating to sharia principles in tourist destinations with local wisdom and help implement the fatwa. Keywords: Halal Tourism, Local Wisdom Context, Fatwa DSN-MUI. Abstrak. Pada tahun 2019 Indonesia meraih peringkat pertama sebagai negara dengan destinasi wisata halal terbaik versi GMTI (Global Muslim Travel Index). Jawa Barat menjadi salah satu provinsi pengembangan Destinasi wisata halal Priorotas Nasional. Namun pada kenyataannya masih terdapat wisata di Jawa Barat yang belum memenuhi kriteria sebagai destinasi wisata halal jika ditinjau dari Fatwa DSN-MUI No.108 Tahun 2016 tentang Pedoman penyelengaraan pariwisata berdasarkan prinsip syariah. Kampung adat Cireundeu yang terletak di Jawa Barat merupakan salah satu destinasi wisata yang memiliki keunikan kearifan lokal. Penelitian ini bertujuan untuk menganalisis praktik wisata halal dalam konteks kearifan lokal di Kampung Adat Cireundeu dengan tinjauan Fatwa DSN-MUI. Metode yang digunakan dalam penelitian ini menggunakan metode penelitian hukum normatif dengan menggunakan pendekatan kualitatif. Teknik pengumpulan data dengan menggunakan Teknik wawancara, studi pustaka serta observasi lapangan. Hasil dari penelitian ini yaitu wisata halal dalam konteks kearifan lokal cukup sulit untuk diimplementasikan di Kampung Adat Cireundeu. Namun bagi Kampung Adat Cireundeu wisata halal bukanlah suatu hal yang harus dihindari oleh pengelola serta masyarakat. Dalam tinjauan oleh Fatwa DSN-MUI pun terdapat beberapa aspek destinasi wisata halal yang tidak sesuai atau terpenuhi pada wisata Kampung Adat Cireundeu. Bagi pihak pengelola akan lebih baik apabila meningkatkan fasilitas seperti pembangunan tempat ibadah yang letaknya strategis dengan pusat wisata, agar memudahkan wisatawan muslim yang akan melaksanakan ibadah. Majelis Ulama Indonesia serta Penyuluh Kementerian Agama sebaiknya melakukan sosialisasi terhadap ketentuan yang berkaitan dengan prinsip syariah pada destinasi wisata dengan kearifan lokal dan membantu pengimplementasian fatwa. Kata Kunci: Wisata Halal, Konteks Kearifan Lokal, Fatwa DSN-MUI.